Strategies for Sustainable Urban Development-Exploring Innovative Approaches for a Liveable Future - Shen, Liyin; Ochoa, Jorge; Bao, Haijun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers various aspects of sustainable urbanisation. It includes empirical evidence, theoretical insights, and practical recommendations in order to inform and inspire sustainable urban strategies. The ten original research studies presented in this reprint explore topics such as green buildings, rail transportation, land-use efficiency, energy consumption, innovation management, heritage preservation, digital technologies, and behaviour change. The interdisciplinary and international scope of the issue reflects the complexity and diversity of the challenges and opportunities encountered when striving for urban sustainability. This Special Issue aimed to provide researchers, practitioners, policymakers, and students with a comprehensive and up-to-date perspective on sustainable urban development.